Integrated molecular analysis of adult Sonic Hedgehog (SHH)-activated medulloblastomas reveals two clinically relevant tumor subsets with VEGFA as potent prognostic indicator - Korshunov, Andrey; Okonechnikov, Konstantin; Stichel, Damian; Ryzhova, Marina; Schrimpf, Daniel; Sahm, Felix; Sievers, Philipp; Absalyamova, Oksana; Zheludkova, Olga; Golanov, Andrey; Jones, David T. W.; Pfister, Stefan; et al. (Neuro-Oncology, 2021)
Up to now, adult medulloblastoma (MB) patients are treated according to the protocols elaborated for pediatric MB although these tumors are different in terms of clinical outcomes and biology. Approximately 70% of adult MB disclose a sonic hedgehog (SHH) molecular signature in contrast to about 30% in pediatric cohorts. In addition, adult SHH-MB (aSHH-MB) are clinically heterogeneous but there is consensus neither on their optimal treatment nor on risk stratification. Thus, the identification of clinically relevant molecular subsets of aSHH-MB and identification of potential treatment targets remains inconclusive.We analyzed 96 samples of institutionally diagnosed aSHH-MB through genome-wide DNA methylation profiling, targeted DNA sequencing, and RNA sequencing to identify molecular subcategories of these tumors and assess their prognostic significance.We defined two aSHH-MB numerically comparable epigenetic subsets with clinical and molecular variability. The subset “aSHH-MBI” (46%/48%) was associated with PTCH1/SMO (54%/46%) mutations, “neuronal” transcriptional signatures, and favorable outcomes after combined radio-chemotherapy (5-year PFS = 80% and OS = 92%). The clinically unfavorable “aSHH-MBII” subset (50%/52%; 5-year PFS = 24% and OS = 45%) disclosed GLI2 amplifications (8%), loss of 10q (22%), and gene expression signatures associated with angiogenesis and embryonal development. aSHH-MBII tumors revealed strong and ubiquitous expression of VEGFA both at transcript and protein levels that was correlated with unfavorable outcome.(1) The histologically uniform aSHH-MB cohort exhibits clear molecular heterogeneity separating these tumors into two molecular subsets (aSHH-MBI and aSHH-MBII), which are associated with different cytogenetics, mutational landscapes, gene expression signatures, and clinical course. (2) VEGFA appears to be a promising biomarker to predict clinical course, which needs further prospective validation as its potential role in the pathogenesis of this subset.
Gesehen am 25.10.2021